Abuse-Deterrent Formulations in Constraining the Abuse Potential of Prescription Medicines: A Myth or Truth - Phaugat, Parmita; Nishal, Suchitra; Dhiman, Rakhi (Current Drug Delivery, 2022)
Background: Diverse pain killers used for the management of varied categories of pain are being misused in order to have extreme pleasant effects by a large number of populations. To overcome the misuse of prescription drugs, regulatory bodies have given stress on the development of abuse resistance. Methods: We studied numerous literatures: (1) Research and review papers including the guidelines for pain management, abuse, and abuse deterrence; (2) Description and categorization of pain along with the management approaches; (3) Advantages and disadvantages of the abuse-deterrent formulations. Results: Abuse-deterrent formulations are the contemporary remedial treatment for pain with reduced prospects of being abused. But these comprise huge expense in contrast to the generic drugs as well as the non-deterrent branded equivalents. Conclusion: Many challenges are faced throughout the development of abuse-deterrent formulations. These formulations displayed a substantial drop in abuse incidences but it may lead to other modes of abuse, which may prove more harmful for the users.
Keywords: Pain